EFFECT OF WORK MOTIVATION, WORK DISCIPLINE AND PERCEPTION OF ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE IN MANYARAN SUB-DISTRICT OFFICE - Sutianingsih Sutianingsih; Theresia Kartika Wuri Handayani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to determine and analyze the effect of work motivation, work discipline and perceptions of organizational support on employee performance at Manyaran Sub-District Office with a quantitative approach. The hypothesis of this study is that work motivation, work discipline and perceived organizational support have a positive and significant effect on employee performance. The population of all employees of Manyaran Sub-District Office is 42 people.using saturated samples. The research instrument used a questionnaire with a Likert scale. The data used are primary and secondary data. To test the quality of the data used validity, reliability, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test. The hhypothesis Testing with Multiple Linear Regression Analysis. The results of hypothesis testing indicate that work motivation and perceived organizational support have a positive and significant effect on employee performance. Work discipline has no significant positive effect on employee performance. Work motivation is the most dominant variable in influencing employee performance. The results of the regression calculation can be seen that the coefficient of determination of Adjusted R Square is 0.888. This means that 88.8% of the variation in employee performance variables can be explained by the variables of work motivation, work discipline and perceived organizational support, while the remaining 11.2% is explained by other variables not proposed in this study. Keywords: work motivation, work discipline, perceived organizational support, employee performance